Ketakutan Interaksi dan Stigma Perawat Terhadap Pasien HIV/AIDS di Masa Pandemi Covid-19 - Yuli Lestari; Tubagus Erwin Nurdiansyah; Renitasari Renitasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Stigma among nurses in people with HIV / AIDS (PLWHA) can reduce the quality of healthcare services for patients. PLWHA service during the Covid-19 pandemic in Lampung Province is referred to as a red zone, which means that the disease transmission process has not been controlled yet, has become limited. Improve the quality of healthcare service for HIV patients during Covid-19 pandemic by eliminating stigma and discrimination. The aim research was to find out related of fear to stigma among nurses concern to HIV patients during Covid-19 pandemic in Dr. H. Abdul Moeloek Lampung Province in 2020. This research use analytic survey design with cross-sectional approach. The population in this study were all nurses in the infection ward, class I until III, VIP, and VVIP in Hospital Dr. H. Abdul Moeloek of Lampung Province 109 nurses. A sample of 97 nurses was taken by simple random technique. The statistical test used the chi square test. The results are stigma among nurses was mostly negative as many as 52 (53.6%); most of nurses had fear on interactions of 57 (58.8%). There is a relationship between fear on interactions with stigma among nurse concern to HIV patients (p value = 0.12, OR = 3.208). Health workers can improve HIV patients’ services during Covid-19 pandemic through emotional management exercises and increase knowledge about HIV patient care during Covid-19 pandemic in order to eliminate stigma of nurses.Keywords: stigma; fear; HIV/AIDS; Covid-19ABSTRAKStigma perawat pada Orang Dengan HIV/AIDS (ODHA) dapat menurunkan kualitas layanan kesehatan pasien. Pelayanan ODHA di masa pandemi Covid-19 di Provinsi Lampung disebut sebagai zona merah yang berarti proses penularan penyakit belum terkendali menjadi dibatasi. Meningkatkan kualitas pelayanan pasien ODHA di masa pandemi Covid-19 dengan menghilangkan stigma dan diskriminasi. Tujuan penelitian diketahui hubungan ketakutan interaksi dengan stigma perawat terhadap pasien HIV di masa pandemi Covid-19 di Rumah Sakit Umum Daerah Dr. H. Abdul Moeloek Provinsi Lampung Tahun 2020. Jenis penelitian menggunakan rancangan survey analitik dengan pendekatan cross-sectional. Populasi penelitian adalah perawat di ruang infeksi kelas I s.d III, VIP dan VVIP RSUD Dr. H. Abdul Moeloek Provinsi Lampung sejumlah 109 perawat. Sampel sebanyak 97 perawat diambil dengan teknik simple random. Uji statistik yang digunakan adalah uji chi square. Hasil Penelitian didapatkan stigma perawat sebagian besar negatif sebanyak 52 (53,6%); sebagian besar perawat memiliki ketakutan interaksi sebanyak 57 (58,8%). Ada hubungan antara ketakutan interaksi dengan stigma perawat terhadap pasien HIV (p value = 0,12, OR = 3,208). Petugas kesehatan dapat meningkatkan pelayanan pasien HIVdi masa pandemi Covid-19 melalui latihan pengelolaan emosional dan meningkatkan pengetahuan tentang perawatan pasien HIV di masa pandemi Covid-19 sehingga diharapkan mampu menghilangkan stigma perawat.Kata kunci: stigma; ketakutan; HIV/AIDS; Covid-19